Diminutives and Hypocoristics as Linguistic and Emotional Markers in Nušić’s “Devetsto petnaesta” - Čutura, Ilijana R.; Dimitrijević, Maja M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper analyzes the use of diminutives and hypocoristics in Branislav Nušić’s Devetsto petnaesta – tragedija jednog naroda, with the aim of examining their stylistic function and their connection to the emotional and thematic layers of the text. The research applies a linguostylistic approach, considering morphological, semantic, and word-formation aspects of these lexemes. Although the work is less discussed in scholarly literature, researchers emphasize its genre hybridity, the presence of religious and biblical motifs, its highly emotional narration, and its thematic focus on collective tragedy. Written from both personal and historical perspectives, the text combines archaisms, folk language, symbolism, and notable lexical and syntactic richness. The use of diminutives and hypocoristics constitutes a significant stylistic feature of the work, appearing in three thematic fields: (1) animals; (2) people (often enhancing empathy and sentimentality); and (3) objects symbolizing light and freedom, where their linguostylistic role is transposed to a symbolic-ideational level. Our analysis shows that these lexemes possess considerable stylistic potential, grounded partly in the style-markedness of certain word-formation models and partly in their correspondence with the overall emotional tone of the text. From the perspective of style-markedness and stylisticity, it becomes clear that the stylisticity of certain diminutives derives from their style-markedness (as in lexemes formed with the suffix -če). At the same time, both style-marked and non-style-marked lexemes achieve their expressive effect within the broader context of the work, functioning as carriers of its exceptional emotionality.
Keywords: diminutives; hypocoristics; Devetsto petnaesta – tragedija jednog naroda; style-markedness; stylisticity